Anatomy Quizbook For students studying or intending to study medicine - Baker, Kerry G. (UTS ePRESS, 2019)
The Anatomy Quizbook is a series of carefully selected questions addressing core learning in clinically relevant anatomy. It provides the opportunity for both pre-med and medical students to improve their knowledge of anatomy, as well as their performance in tests and examinations. The form of self-testing presented in the Anatomy Quizbook has many benefits: it is proven to aid retention (Lieberman 2012), it is a very useful method to apply at regular intervals to ensure robust knowledge, and it is extremely beneficial in determining what is known before rather than after a test or exam. Bearing in mind that it is neither necessary nor advisable to learn everything there is to know about anatomy, it is intended that the Anatomy Quizbook be used in conjunction with a comprehensive anatomy textbook such as Clinically Oriented Anatomy (Moore et al, 2014) or Gray's Anatomy for Students (Drake et al, 2015). And whilst the Anatomy Quizbook is intended primarily for students, tutors may also find this a very useful teaching resource.